2012
DOI: 10.1128/aac.05991-11
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study of the Impact of Carbapenem Resistance on Mortality in Pseudomonas aeruginosa Bloodstream Infections

Abstract: The impact of antimicrobial resistance on clinical outcomes is the subject of ongoing investigations, although uncertainty remains about its contribution to mortality. We investigated the impact of carbapenem resistance on mortality in Pseudomonas aeruginosa bacteremia in a prospective multicenter (10 teaching hospitals) observational study of patients with monomicrobial bacteremia followed up for 30 days after the onset of bacteremia. The adjusted influence of carbapenem resistance on mortality was studied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 39 publications
7
115
3
1
Order By: Relevance
“…49,50 We identified, however, a higher risk of mortality associated with CR BSIs in neutropenic patients compared with CS infections. These data are yet to Systematic review JAC be confirmed in large prospective studies and have often been attributed to inadequate therapy.…”
Section: Europementioning
confidence: 56%
“…49,50 We identified, however, a higher risk of mortality associated with CR BSIs in neutropenic patients compared with CS infections. These data are yet to Systematic review JAC be confirmed in large prospective studies and have often been attributed to inadequate therapy.…”
Section: Europementioning
confidence: 56%
“…Although the current study specifically evaluated the effects of combination therapy, the identified risk factors for death within 30 days have significant implications for the prevention and treatment of carbapenem-resistant Gram-negative bacteremia (8,24,33,34). Additionally, because the current study included only ICU patients, the risk factors further inform the treatment of this patient population, for which ICU admission is already a wellknown risk factor for death (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…The lesions reportedly are localized on gluteal, and perineal regions, extremities, neck, trunk, and face (8). Mortality rates for EG range from 15% to as high as 77% based on reports in the literature (9). Currently, a large local excision, and antibiotherapy are recommended as soon as the diagnosis is established.…”
Section: Discussionmentioning
confidence: 99%